Analysis of arbovirus isolates from Australia identifies novel bunyaviruses including a mapputta group virus from Western Australia that links gan gan and maprik viruses - Briese, T.; Williams, D.; Kapoor, V.; Diviney, S.; Certoma, A.; Wang, J.; Johansen, C.; Chowdhary, R.; Mackenzie, John; Lipkin, W. (Public Library of Science, 2016)
The Mapputta group comprises antigenically related viruses indigenous to Australia and Papua New Guinea that are included in the family Bunyaviridae but not currently assigned to a specific genus. We determined and analyzed the genome sequences of five Australian viruses isolated from mosquitoes collected during routine arbovirus surveillance in Western Australia (K10441, SW27571, K13190, and K42904) and New South Wales (12005). Based on matching sequences of all three genome segments to prototype MRM3630 of Trubanaman virus (TRUV), NB6057 of Gan Gan virus (GGV), and MK7532 of Maprik virus (MPKV), isolates K13190 and SW27571 were identified as TRUV, 12005 as GGV, and K42904 as a Mapputta group virus from Western Australia linking GGV and MPKV. The results confirmed serum neutralization data that had linked SW27571 to TRUV. The fifth virus, K10441 from Willare, was most closely related to Batai orthobunyavirus, presumably representing an Australian variant of the virus. Phylogenetic analysis also confirmed the close relationship of our TRUV and GGV isolates to two other recently described Australian viruses, Murrumbidgee virus and Salt Ash virus, respectively. Our findings indicate that TRUV has a wide circulation throughout the Australian continent, demonstrating for the first time its presence in Western Australia. Similarly, the presence of a virus related to GGV, which had been linked to human disease and previously known only from the Australian southeast, was demonstrated in Western Australia. Finally, a Batai virus isolate was identified in Western Australia. The expanding availability of genomic sequence for novel Australian bunyavirus variants supports the identification of suitably conserved or diverse primer-binding target regions to establish group-wide as well as virus-specific nucleic acid tests in support of specific diagnostic and surveillance efforts throughout Australasia.